If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying W + 76 + w = 129 Reorder the terms: 76 + W + w = 129 Solving 76 + W + w = 129 Solving for variable 'W'. Move all terms containing W to the left, all other terms to the right. Add '-76' to each side of the equation. 76 + W + -76 + w = 129 + -76 Reorder the terms: 76 + -76 + W + w = 129 + -76 Combine like terms: 76 + -76 = 0 0 + W + w = 129 + -76 W + w = 129 + -76 Combine like terms: 129 + -76 = 53 W + w = 53 Add '-1w' to each side of the equation. W + w + -1w = 53 + -1w Combine like terms: w + -1w = 0 W + 0 = 53 + -1w W = 53 + -1w Simplifying W = 53 + -1w
| (9x)/(6x-11) | | 8=x-1+2x | | ((9x)/(6x-11)) | | 13a-7= | | 2x+1500=x+1000 | | (1/2x+3/4)+(1/2x-1/4) | | 6x+8y=2 | | (3t)/(t-2)(3t-6)/(t^2) | | 8(3x+1)= | | (9x)/6x-11 | | (x-5)+17=15 | | 15x+45=75 | | 5z-13=-3 | | x*5=x+150 | | 3(j-k)= | | (9x)/6x-1 | | N+10=6-8n | | 5-2x=3x-2 | | N-10=8n-6 | | -2x+4=2+8 | | 5x+3x=28 | | 4x+2=6-x | | 10-n=6-8n | | 9.10-0.8= | | 3(3.30+2.50)=55.20 | | 3x+7x=-120 | | 10x-7=9-4x | | 10-n=8n-6 | | (3x+1)/(6x-2)=(2x+5)/(4x-13) | | 4x+10=5x-3 | | -8(m+6)+2=-7(3m+1) | | 7(5n+3)= |